Large Converse Piezoelectric Effect Measured on a Single Molecule on a Metallic Surface - Stetsovych, Oleksandr; Mutombo, Pingo; Švec, Martin; Šámal, Michal; Nejedlý, Jindřich; Císařová, Ivana; Vázquez, Héctor; Moro-Lagares, María; Berger, Jan; Vacek, Jaroslav; Stará, Irena G; Starý, Ivo; et al. (Journal of the American Chemical Society, 2018)
The converse piezoelectric effect is a phenomenon in which mechanical strain is generated in a material due to an applied electrical field. In this work, we demonstrate the converse piezoelectric effect in single heptahelicene-derived molecules on the Ag(111) surface using atomic force microscopy (AFM) and total energy density functional theory (DFT) calculations. The force-distance spectroscopy acquired over a wide range of bias voltages reveals a linear shift of the tip-sample distance at which the contact between the molecule and tip apex is established. We demonstrate that this effect is caused by the bias-induced deformation of the spring-like scaffold of the helical polyaromatic molecules. We attribute this effect to coupling of a soft vibrational mode of the molecular helix with a vertical electric dipole induced by molecule-substrate charge transfer. In addition, we also performed the same spectroscopic measurements on a more rigid o-carborane dithiol molecule on the Ag(111) surface. In this case, we identify a weaker linear electromechanical response, which underpins the importance of the helical scaffold on the observed piezoelectric response.